Biology and life table parameters of some phytoseiid mites fed on Oligonychus mangiferus (Acari: Tetranychidae) - Shimaa F. Fahim; Faten M. Momen (Persian Journal of Acarology)
The mango red spider mite, Oligonychus mangiferus, is a dangerous pest of mango that causes an indirect reduction in the production and quality of mango fruits. Since there is an urgent need to control O. mangiferus, searching for native phytoseiids that can prey on O. mangiferus may provide promising results in the biological control of this mite pest. In this study, biological and life table parameters of the predatory mites Cydnoseius negevi, Neoseiulus barkeri, Paraseiulus talbii, and Typhlodromus athiasae were determined when fed on O. mangiferus under laboratory conditions. Cydnoseius negevi, N. barkeri, and T. athiasae were successfully fed and developed on O. mangiferus, while P. talbii failed to develop on O. mangiferus. The pre-adult duration did not differ significantly among the three phytoseiids. The longest female longevity was 40.28 days for N. barkeri, while the shortest was 26.04 days for C. negevi. The lowest daily fecundity was observed in N. barkeri females, whereas the highest was oviposited by C. negevi and T. athiasae. Statistically, Typhlodromus athiasae had the maximum intrinsic rate of increase (r) and finite rate of increase (λ), followed by N. barkeri and C. negevi. The shortest mean generation time (T) and the lowest net reproductive rate (R0) were reported for C. negevi. In conclusion, C. negevi, N. barkeri, and T. athiasae successfully fed, developed and sustained oviposition on O. mangiferus. Therefore, they could be considered as important biological control agents of O. mangiferus.